Acreditação hospitalar: cenário nacional, atual e potencialidades para o cuidar em saúde, um olhar a partir do campo CTS - Silva, Adriana Bayeux da (Universidade Federal de São Carlos, 2026)
Hospital organizations are well-known for their concern in ensuring safety and quality in the services provided to their users. The use of tools to evaluate these services emerges in this context. Thus, this research aims to investigate the current national scenario of Hospital Accreditation and relate the findings to the care model produced in the health field. A Systematic Literature Review was conducted through a search in databases, using the descriptors: Hospital Quality, Hospital Quality Certification, and Hospital Accreditation. The following filters were applied: full text and availability, documents of the scientific article type, and publication year from 2019 to 2024. The PRISMA 2020 flowchart was applied, and an analytical framework was constructed to organize the material. This research sought to delve into the field of Science, Technology, and Society, connecting it to the field of Health, considering that the latter uses science and technology to protect, restore, and maintain the health, well-being, and quality of life of people in society. Therefore, it was important to address, along this path, some concepts about work in healthcare (its protagonists and products), the technological apparatus involved, and the healthcare system that structures the process of seeking a cure, reducing pain and suffering, and rehabilitating and maintaining life, within the Brazilian context. Thus, the programs and organizations that work in the accreditation and certification process of healthcare services in Brazil were analyzed in an attempt to relate them to the technologies involved in healthcare.
Hospital accreditation: national scenario, current situation, and potential for healthcare, a perspective from the Science, Technology, and Society (STS) field
Keywords: Qualidade da assistência à saúde; Gestão de ciência; Tecnologia e inovação em saúde; Acreditação hospitalar; Quality of healthcare; Management of science; Technology and innovation in health; Hospital accreditation; CIENCIAS DA SAUDE; 3. Saúde e Bem-Estar